Chaotic and Fast Audiovisuals Increase Attentional Scope but Decrease Conscious Processing. (1st December 2018) - Andreu-Sánchez, Celia; Martín-Pascual, Miguel Ángel; Gruart, Agnès; Delgado-García, José María
Highlights: Cuts affect viewers' attention and brain connectivity while watching media content. Organized style of edition presents greater activity in viewers' frontal areas. Non-organized style of edition provokes a higher activity in visual areas. Abstract: Audiovisual cuts involve spatial, temporal, and action narrative leaps. They can even change the meaning of the narrative through film editing. Many cuts are not consciously perceived, others are, just as we perceive or not the changes in real events. In this paper, we analyze the effects of cuts and different editing styles on 36 subjects, using electroencephalographic (EEG) techniques and the projection of stimuli with different audiovisual style of edition but the same narrative. Eyeblinks, event-related potentials (ERPs), EEG spectral power and disturbances, and the functional and effective connectivity before and after the cuts were analyzed. Cuts decreased blink frequency in the first second following them. Cuts also caused an increase of the alpha rhythm, with a cortical evolution from visual toward rostral areas. There were marked differences between a video-clip editing style, with greater activities evoked in visual areas, and the classic continuous style of editing, which presented greater activities in the frontal zones. This was reflected by differences in the theta rhythm between 200 and 400 ms, in visual and frontal zones, and can be connected to the different demands that each style of edition makes on working memory and conscious processing after cutting. Also, at the time of cuts, the causality between visual, somatosensory, and frontal networks is altered in any editing style. Our findings suggest that cuts affect media perception and chaotic and fast audiovisuals increase attentional scope but decrease conscious processing.